DNS of Wall-Bounded Turbulent Flows A First Principle Approach - Sengupta, Tapan K.; Bhaumik, Swagata; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights by careful documentation of developments what led to tracking the growth of deterministic disturbances inside the shear layer from receptivity to fully developed turbulent flow stages. Associated theoretical and numerical developments are addressed from basic level so that an uninitiated reader can also follow the materials which lead to the solution of a long-standing problem. Solving Navier-Stokes equation by direct numerical simulation (DNS) from the first principle has been considered as one of the most challenging problems of understanding what causes transition to turbulence. Therefore, this book is a very useful addition to advanced CFD and advanced fluid mechanics courses.
DNS of Wall-Bounded Turbulent Flow: An Introduction -- DNS of Navier-Stokes Equation -- Receptivity and Instability.-Nonlinear Theoretical and Computational Analysis of Fluid Flows -- Dynamics of the Spatio-Temporal Wave-Front in 2D Framework -- 3D Routes of Transition to Turbulence by STWF.
Keywords: Fluid mechanics; Engineering mathematics; Engineering -- Data processing; Mathematical physics; Continuum mechanics; Engineering Fluid Dynamics; Mathematical and Computational Engineering Applications; Theoretical, Mathematical and Computational Physics; Continuum Mechanics